2010
DOI: 10.1152/ajpheart.00876.2009
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of BKCa channels to local metabolic coronary vasodilation: effects of metabolic syndrome

Abstract: This investigation was designed to examine the hypothesis that impaired function of coronary microvascular large-conductance Ca(2+)-activated K(+) (BK(Ca)) channels in metabolic syndrome (MetS) significantly attenuates the balance between myocardial oxygen delivery and metabolism at rest and during exercise-induced increases in myocardial oxygen consumption (MVo(2)). Studies were conducted in conscious, chronically instrumented Ossabaw swine fed a normal maintenance diet (11% kcal from fat) or an excess calori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 51 publications
2
35
0
Order By: Relevance
“…(84) Importantly, these changes occur prior to any evidence of overt atherosclerotic disease and have been associated with diminished diastolic and systolic contractile function in obese/MetS in humans(47, 86, 87) and in animal models. (20, 57, 88) These findings indicate that underlying coronary microvascular dysfunction likely contributes to reductions in cardiac contractile function,(45, 47, 48, 51) to concentric ventricular hypertrophy,(41, 44-48, 89) and to the significant increases in risk of myocardial infarction(17) and cardiovascular mortality(8, 90, 91) observed in obese individuals with the MetS.…”
Section: Microvascular Dysfunction In Obesity and The Metabolic Syndromementioning
confidence: 93%
See 1 more Smart Citation
“…(84) Importantly, these changes occur prior to any evidence of overt atherosclerotic disease and have been associated with diminished diastolic and systolic contractile function in obese/MetS in humans(47, 86, 87) and in animal models. (20, 57, 88) These findings indicate that underlying coronary microvascular dysfunction likely contributes to reductions in cardiac contractile function,(45, 47, 48, 51) to concentric ventricular hypertrophy,(41, 44-48, 89) and to the significant increases in risk of myocardial infarction(17) and cardiovascular mortality(8, 90, 91) observed in obese individuals with the MetS.…”
Section: Microvascular Dysfunction In Obesity and The Metabolic Syndromementioning
confidence: 93%
“…(102) MetS is also associated with alterations in the functional expression of, and electromechanical coupling between, voltage-dependent K + and Ca 2+ channels. (7, 83, 84, 88, 103, 104) Continued research to elucidate the precise mechanisms responsible for the deleterious impact of the MetS on microvascular function is needed, and stands to provide novel targets for directed therapies needed to treat the pathologic consequences of this multifactorial syndrome.…”
Section: Microvascular Dysfunction In Obesity and The Metabolic Syndromementioning
confidence: 99%
“…The increase in baseline flow in this group of metabolic syndrome swine is puzzling but could be related to alterations in substrate utilization, internal work of the myocardium, and/or cardiac efficiency. Although these variables were not assessed in this group of animals, a recent study by our laboratory found that a trend for an increase in baseline flow in conscious, metabolic syndrome swine was associated with a reduction in average lactate uptake and cardiac index with no difference in myocardial oxygen consumption, i.e., altered substrate utilization and cardiac efficiency (5). It is important to recognize that the 21 Ϯ 1% stenosis in metabolic syndrome swine did not limit flow during hyperemia, since the peak hyperemic response (i.e., the minimum vascular resistance) and volume of repayment were not different between lean and metabolic syndrome swine (Table 2).…”
Section: Effect Of Metabolic Syndrome On Ischemic Coronary Vasodilationmentioning
confidence: 94%
“…Coronary vascular dysfunction in MetS is related to impaired BK (Ca) channel function and is accompanied by significant increases in L-type Ca 2+ channel-mediated coronary vasoconstriction [5]. In another study of this research group, penitrem A (10µg/kg, i.v) revealed that the exercise-induced increases in blood pressure were significantly elevated in MetS swine [6]. and NAFLD indicate that the clearance and metabolism of fungal mycotoxins are linked to hypercholesterolemia and amyloid beta oligomers.…”
Section: Mycotoxins Causing Msmentioning
confidence: 88%